2022
DOI: 10.1186/s13018-022-02952-6
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic comparison between perineural and intravenous dexamethasone for shoulder arthroscopy: a meta-analysis of randomized controlled trials

Abstract: Introduction The analgesic comparison between perineural and intravenous dexamethasone on interscalene block for pain management after shoulder arthroscopy remains controversial. We conduct this meta-analysis to explore the influence of perineural versus intravenous dexamethasone on interscalene block for pain control after shoulder arthroscopy. Methods We have searched PubMed, Embase, Web of science, EBSCO and Cochrane library databases through Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…One meta-analysis suggested that a higher concentration of perineural dexamethasone than that of intravenous dexamethasone might be required to achieve analgesic efficacy. 19 However, there is no rationale for using off-label perineural dexamethasone if a higher concentration is needed to produce a systemic effect equivalent to that of intravenous dexamethasone. Lastly, some authors have described the risk of exacerbated local anesthetic-induced hyperalgesia following co-administration of perineural dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…One meta-analysis suggested that a higher concentration of perineural dexamethasone than that of intravenous dexamethasone might be required to achieve analgesic efficacy. 19 However, there is no rationale for using off-label perineural dexamethasone if a higher concentration is needed to produce a systemic effect equivalent to that of intravenous dexamethasone. Lastly, some authors have described the risk of exacerbated local anesthetic-induced hyperalgesia following co-administration of perineural dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on these physiological similarities between the soft tissue microenvironment after surgery and CRPS, we applied a combination of steroid and mannitol treatment used for CRPS to reduce postoperative edema and pain. Steroids are a popular postoperative adjunct in facial and musculoskeletal operations due to the high tendency for edema development in the face and extremities [24][25][26][27][28]. Steroids inhibit the expression of proinflammatory cytokines and the production of inflammatory mediators such as prostaglandins [23].…”
Section: Discussionmentioning
confidence: 99%